Evaluating Projects and Assessing Sustainable Development in Imperfect Economies - Kenneth Arrow; Partha Dasgupta; Karl-Göran Mäler (Fondazione Eni Enrico Mattei (FEEM), 2003)
We are interested in three related questions: (1) How should accounting prices be estimated? (2) How should we evaluate policy change in an imperfect economy? (3) How can we check whether intergenerational well-being will be sustained along a projected economic programme? We do not presume that the economy is convex, nor do we assume that the government optimizes on behalf of its citizens. We show that the same set of accounting prices should be used both for policy evaluation and for assessing whether or not intergenerational welfare along a given economic path will be sustained. We also show that a comprehensive measure of wealth, computed in terms of the accounting prices, can be used as an index for problems (2) and (3) above. The remainder of the paper is concerned with rules for estimating the accounting prices of several specific environmental natural resources, transacted in a few well known economic institutions.
Keywords: D6; D9; E2; O2; O4; Q2; Q3; 330; Sustainable development; Imperfect economies; Projektbewertung; Nachhaltige Entwicklung; Umweltbewertung; Theorie